Reproductive Rights and Childfree in Islamic Law: A Juridical and Social Analysis - Ramadhan, Abdul Rahman (Proceeding International Conference on Religion, Science and Education, 2025)
This research aims to identify and define the concept of reproductive rights in Islamic law, analyze Islamic legal views on childfree decisions and examine the social implications of childfree decisions. Reproductive rights are an important part of human rights that include the right to make free and responsible decisions regarding the number, spacing and timing of children. However, in the context of Islamic law, the decision not to have children can give rise to a variety of complex legal and social interpretations. The trend of going childfree is increasing in many countries, including Muslim-majority countries. This decision is often influenced by various factors such as economics, health, and personal preference. However, in Muslim societies, this decision can conflict with traditional norms that encourage marriage and childbearing. This research uses a qualitative approach with literature review data literature review. The results of this research show that reproductive rights are recognized in Islamic law, although there are variations in interpretation regarding their limits and application. The decision to go childfree is acceptable within the framework of Islamic law if it is based on valid reasons and does not contradict the principles of sharia. However, the social perception and stigmatization of this decision remains a challenge in many Muslim communities. This research can make an important contribution to the understanding of reproductive rights and childfree decisions in the context of Islamic law. The results of this research are expected to help reduce social stigma towards individuals who choose not to have children and encourage the development of more inclusive and evidence-based policies in Muslim-majority countries, especially Indonesia.